Credibility For Sale - Harris Dellas; Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2013)
We develop a sovereign debt model with offcial and private creditors where default risk depends on both the level and the composition of liabilities. Higher exposure to offcial lenders improves incentives to repay but carries extra costs, such as reduced ex-post flexibility. The model implies that official lending to sovereigns takes place in times of debt distress; carries a favorable rate; and can displace private funding even under pari passu provisions. Moreover, in the presence of long-term debt overhang, the availability of offcial funds increases the probability of default on existing debt, although default does not trigger exclusion from private credit markets. These findings help shed light on joint default and debt composition choices of the type observed during the recent sovereign debt crisis in Europe.
Keywords: F34; H63; 330; Sovereign debt; Official lending; Default; Enforcement; Öffentliche Schulden; Kreditrisiko; Glaubwürdigkeit; Kreditgeschäft; Schuldenkrise; Theorie